Geospatial evaluation of river basin small hydropower potential using AHP - Korkmaz, Meral (Frontiers in Environmental Science, 2026)
This study develops an integrated Geographic Information Systems (GIS) and Analytic Hierarchy Process (AHP) framework to accurately identify small hydropower plants sites that support sustainable water–energy planning. The approach is applied to the Peri River Basin in Eastern Türkiye by combining multisource remote sensing datasets with a semi-automated narrow-valley detection technique to enhance the spatial precision of site selection. Nine hydrological and physiographic criteria including stream order, rainfall, slope, geology, drainage density, elevation, land use land cover, Stream Power Index SPI and Topographic Wetness Index TWI were weighted using the AHP method to generate a five-class suitability map for small hydropower plants development. A major contribution of this study is the explicit integration of valley morphology into the conventional GIS–AHP workflow, which significantly improves the identification of hydropower favorable river segments. Results indicate that approximately 3% of the basin exhibits very high suitability, while 46% is moderately suitable for run-of-river small hydropower plants development. Model validation was performed by overlaying the suitability map with the locations of existing dams/hydropower facilities, showing that current facilities are mainly located in high-suitability zones. Separately, the workflow identified 13 newly proposed high-suitability candidate dam sites (P1–P13), selected from screened suitable dam points using narrow-valley detection criteria. By minimizing ecological disturbance and aligning with watershed-based management principles, the proposed GIS-supported multicriteria method provides a transferable and cost-effective decision-support tool for small-hydropower planning in rural and mountainous basins, offering practical contributions to sustainable resource management and the water–energy nexus.